Technical efficacy and local recurrence after stereotactic radiofrequency ablation of 2653 liver tumors: a 15-year single-center experience with evaluation of prognostic factors. (31st December 2022) - Schullian, Peter; Laimer, Gregor; Johnston, Edward; Putzer, Daniel; Eberle, Gernot; Scharll, Yannick; Widmann, Gerlig; Kolbitsch, Christian; Bale, Reto
Abstract: Purpose: To assess the technical outcome and local tumor control of multi-probe stereotactic radiofrequency ablation (SRFA) in a large series of patients. Furthermore, to determine factors accounting for adverse outcomes. Material and methods: Between 2003 and 2018, 865 patients were treated by SRFA for 2653 primary and metastatic liver tumors with a median tumor size of 2.0 cm (0.5 − 19 cm). Primary technical efficacy (PTE) and local recurrence (LR) were evaluated, and possible predictors for adverse events analyzed using uni- and multi-variable binary logistic regression. Results: Overall, 2553 of 2653 tumors were successfully ablated at initial SRFA resulting in a PTE rate of 96.2%. Predictors of lower PTE rates were age > 70 years, tumor size > 5 cm, number of probes, location close to liver capsule/organs and segment II. LR occurred in 220 of 2653 tumors (8.3%) with the following predictors: age, tumor type/size, conglomerates, segments I/IVa/IVb, number of probes and location close to major vessels/bile duct. Multivariable analysis revealed tumor size > 5 cm (odds ratio [OR] 3.153), age > 70 years (OR 1.559), and location in segment II (OR 1.772) as independent prognostic factors for PTE, whereas tumor location close to major vessels (OR 1.653) and in segment IVb (OR 2.656) were identified as independent prognostic factors of LR. Conclusions: Stereotactic RFA is an attractive option in the management of primary or metastatic liver tumors with good local tumor control, even in large tumors. The presented prognostic factors for adverse local oncological outcome might help to stratify unfavorable tumors for ablation.